FACTORS THAT INFLUENCE PURCHASE DECISION AT COFFE SHOP DUKKU RIANG COFFEE MEDAN - Gita Ayu Lestari; Endang Sulistya Rini; Syafrzal Helmi Situmorang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Coffee is one of the strategic commodities in the plantation sub-sector that has high economic value. The development of the coffee shop business in Medan City has led to competition in the coffee shop sector which has caused consumers to be more selective and can easily move from one coffee shop to another to decide to buy coffee. The increase in competition requires companies to highlight their own characteristics and uniqueness in order to be superior to other companies that offer similar products and of course attract consumers' attention. Therefore, management needs to pay attention to and consider the store atmosphere if they want to attract, entice, or encourage consumers to visit the cafe so that consumer satisfaction will be realized and consumers will be interested in visiting. The data analysis technique in this study was carried out with classical assumptions and multiple linear regression tests. The results of this study indicate that the Lifestyle Variable has a coefficient value of 0.714 indicating that the more relevant the consumer's lifestyle is to the products or services offered, the more likely consumers will make a decision to buy. The Brand Image variable has a coefficient value of 0.309 indicating that positive consumer perceptions of the brand can increase consumer decisions to buy and the Store Atmosphere variable has a coefficient value of -0.284 indicating a significant negative influence, meaning that the worse the store atmosphere, the less likely consumers will decide to buy. Overall, consumer decisions are greatly influenced by a combination of lifestyle, brand image, and cafe atmosphere. Therefore, an integration strategy of these three aspects needs to be carried out consistently.